"God is the giver and taker of life": Muslim beliefs and attitudes regarding assisted suicide and euthanasia. Issue 1 (2nd January 2018) - Ahaddour, Chaïma; Van den Branden, Stef; Broeckaert, Bert
ABSTRACT: In the context of the Belgian debates on end-of-life care, the views of Muslims remain understudied. The aim of this article is twofold. First, we seek to document the relation between contemporary normative Muslim ideas on assisted suicide and voluntary euthanasia on the one hand and real-world views and attitudes of Muslims living in Belgium on the other hand. Second, we aim to identify whether a shift is observable in the views and attitudes regarding active termination of life between first- and second-generation Muslims. We have observed that when dealing with these bioethical issues, both first- and second-generation Muslims adopt a theological line of reasoning similar to the one that can be found in normative Islamic views. We have found an absolute rejection of every act that deliberately terminates life, based upon the unconditional belief in an afterlife and in God's sovereign power over life and death.